how to solve the quadratic function step-by-step

first set it equal to zero, so we have 6x

^{2}-2x+1=0.The quadratic equation tells us that x=(-b+

_{-}(b^{2}-4ac)^{.5})/2a.Where a is the coefficient in front of the x

^{2}, b is the coefficient in front of the x, and c is the constant.Raising something to the .5 power is the same as taking the square root of that number.

So we get x=(2+

_{-}(4-4(6)(1))^{.5})/12=(2^{+}_{-}(-20)^{.5})/12=(2^{+}_{-}(-4)^{.5}(5)^{.5})/12=(2^{+}_{-}(2i)(5)^{.5})/12=(1+(5)

^{.5}i)/6 and (1-(5)^{.5}i)/6.Where i=(-1)

^{.5}which is an imaginary number used in complex analysis.